Xây dựng lược đồ sai phân suy rộng tựa đơn điệu có độ đúng cấp cao cho một số phương trình - A, Dang Quang (Journal of Computer Science and Cybernetics, 2018)
In this paper with the help of the asymptotic error expansion to finite difference schemes for nonstationary problems and the corollaries of the differential equations we have constructed generalized difference schemes quasimonotone and having high order of accuracy for some equations and system.